Strategi Pengembangan UMKM Keripik Tempe Kitaram Melalui Peningkatan Kualitas SDM Di Kec. Blimbing, Kota Malang - Dayat, Farhan; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Micro, Small, and Medium Enterprises (MSMEs) are crucial for Indonesia's economic development. This importance arises from their role as a socio-economic platform for communities, their substantial contribution to job creation, and their involvement in income distribution. The significant potential of MSMEs to stimulate economic activity and serve as a primary source of income for the majority of the population, thereby improving their welfare, makes them strategically significant as the backbone of the people's economy Research ObjectiveThe study aims to explore the development strategies for the Kintaram Tempe Chips MSME by enhancing human resource (HR) quality in Blimbing Sub-district, Malang City.Research Methodology A qualitative research methodology, specifically a descriptive study design, is employed. Three pathways are identified in the Kintaram Tempe Chips MSME's efforts to improve HR quality for its employees.Training Practices Using On-The-Job and Demonstration-and-Example ApproachesIn the On-The-Job approach, the owner instructs new employees to observe experienced staff performing their tasks, after which they are expected to replicate what they have seen.The Demonstration-and-Example technique involves the owner demonstrating and explaining the steps required to complete specific tasks.Educational Activities The Kintaram Tempe Chips MSME employs Coaching and Counseling as a short-term educational procedure for staff members. Through this approach, the owner imparts skills and knowledge to their subordinates.Work ExperienceThe owner gives preference to applicants with prior work experience. However, they remain willing to hire individuals without such experience, providing opportunities for skill development. Keywords : Strategy,Tempe Chips MSMEs,Human Resources (HR)